2020
DOI: 10.1002/1873-3468.13778
|View full text |Cite
|
Sign up to set email alerts
|

ddhCTP produced by the radical‐SAM activity of RSAD2 (viperin) inhibits the NAD+‐dependent activity of enzymes to modulate metabolism

Abstract: Edited by Peter BrzezinskiRadical S-adenosylmethionine (SAM) domain-containing protein 2 (RSAD2; viperin) is a key enzyme in innate immune responses that is highly expressed in response to viral infection and inflammatory stimuli in many cell types. Recently, it was found that RSAD2 catalyses transformation of cytidine triphosphate (CTP) to its analogue 3 0 -deoxy-3 0 ,4 0 -didehydro-CTP (ddhCTP). The cellular function of this metabolite is unknown. Here, we analysed the extra-and intracellular metabolite leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Incorporation of ddhCTP into RNA prevents further extension of the RNA template, thereby inhibiting virus replication (Minton, 2018). However, more recent studies showed that, rather than acting as a chain terminator, ddhCTP may restrict viral replication through inhibition of the NAD + -dependent enzymatic activities and regulation of inflammatory responses, including the cellular level of TNF-α (Van Gool et al, 2009;Honarmand et al, 2020). Inhibition of NAD + -dependent enzymatic reactions by ddhCTP may also induce the ADP ribosylation, promoting the degradation of viral proteins (Ullrich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of ddhCTP into RNA prevents further extension of the RNA template, thereby inhibiting virus replication (Minton, 2018). However, more recent studies showed that, rather than acting as a chain terminator, ddhCTP may restrict viral replication through inhibition of the NAD + -dependent enzymatic activities and regulation of inflammatory responses, including the cellular level of TNF-α (Van Gool et al, 2009;Honarmand et al, 2020). Inhibition of NAD + -dependent enzymatic reactions by ddhCTP may also induce the ADP ribosylation, promoting the degradation of viral proteins (Ullrich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…RSAD2 is a key enzyme in innate immune responses that is highly expressed in response to viral infection and inflammatory stimuli in many cell types. 28 Among human THP‐1‐induced macrophages, RSAD2 is upregulated in M1 subtype macrophages, indicating a correlation between RSAD2 and M1‐like polarization. 29 Our study found that inhibition of RSAD2 by miR‐3184 in macrophages induced M2‐like polarization.…”
Section: Discussionmentioning
confidence: 99%
“…We determined that Radical S‐adenosylmethionine (SAM) domain‐containing protein 2 (RSAD2) downregulated is one of the most significant genes and may be the directly downstream targets of miR‐3184‐3p. RSAD2 is a key enzyme in innate immune responses that is highly expressed in response to viral infection and inflammatory stimuli in many cell types 28 . Among human THP‐1‐induced macrophages, RSAD2 is upregulated in M1 subtype macrophages, indicating a correlation between RSAD2 and M1‐like polarization 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-localization of viperin and the viral RNA polymerase at the ER membrane would be expected to increase the local concentration of ddhCTP. Other studies from the same laboratory provided preliminary evidence that ddhCTP may act as an inhibitor of several NAD 1 -dependent dehydrogenases, including glyceraldehyde-3-phosphate dehydrogenase, lactate dehydrogenase, and malate dehydrogenase (78). But whether the inhibitory effects of ddhCTP have physiological relevance and how such broad-brush inhibition of primary metabolism might restrict viral infection are unclear.…”
Section: Elucidation Of the Substrate For Viperinmentioning
confidence: 99%